2005
DOI: 10.1176/jnp.17.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Spectroscopy of Memory and Frontal Brain Region in Early Multiple Sclerosis

Abstract: In vivo proton magnetic resonance spectroscopy (1H-MRS) has been used to assess biochemical changes that occur in demyelinating lesions and in normal appearing white matter (NAWM) in multiple sclerosis (MS) patients. N-acetylaspartate (NAA) levels in MS patients may indicate neural viability. In early stages of MS, patients may suffer from slight cognitive impairment. The objective of this study was to investigate memory function in relation to biochemical properties of frontal brain areas of MS patients. Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…Creatine-referenced N-acetyl aspartate has shown reductions relative to control in mixed or unspecified multiple sclerosis lesions (2235), white matter (36), normal-appearing white matter (22, 24, 25, 30, 34, 3746), and mixed tissue (47); in relapsing-remitting multiple sclerosis lesions (4856), white matter (36, 54, 5764), normal-appearing white matter (48, 5052, 6570), gray matter (54, 70), mixed tissue (54, 58, 63, 7175), and spine (76); and in progressive multiple sclerosis lesions (50, 52, 77–79), white matter (36, 60, 62, 80), normal-appearing white matter (45, 46, 50, 52, 66, 69, 78, 79, 81, 82), gray matter (83), and mixed tissue (71, 73, 8489). In addition, N-acetyl aspartate quantified as institutional units or relative to non-creatine references like water or phantom acquisitions has been shown to decrease in mixed or unspecified multiple sclerosis lesions (22, 29, 90–96), white matter (97, 98), normal-appearing white matter (22, 91, 94, 99105), gray matter (94, 100, 103, 104, 106), mixed tissue (107, 108), spine (109112), and whole-brain measures (113, 114); in relapsing-remitting lesions (50, 53, 96, 115–…”
Section: Potential Small-molecule Diagnostic Biomarkers Of Multiple Smentioning
confidence: 99%
“…Creatine-referenced N-acetyl aspartate has shown reductions relative to control in mixed or unspecified multiple sclerosis lesions (2235), white matter (36), normal-appearing white matter (22, 24, 25, 30, 34, 3746), and mixed tissue (47); in relapsing-remitting multiple sclerosis lesions (4856), white matter (36, 54, 5764), normal-appearing white matter (48, 5052, 6570), gray matter (54, 70), mixed tissue (54, 58, 63, 7175), and spine (76); and in progressive multiple sclerosis lesions (50, 52, 77–79), white matter (36, 60, 62, 80), normal-appearing white matter (45, 46, 50, 52, 66, 69, 78, 79, 81, 82), gray matter (83), and mixed tissue (71, 73, 8489). In addition, N-acetyl aspartate quantified as institutional units or relative to non-creatine references like water or phantom acquisitions has been shown to decrease in mixed or unspecified multiple sclerosis lesions (22, 29, 90–96), white matter (97, 98), normal-appearing white matter (22, 91, 94, 99105), gray matter (94, 100, 103, 104, 106), mixed tissue (107, 108), spine (109112), and whole-brain measures (113, 114); in relapsing-remitting lesions (50, 53, 96, 115–…”
Section: Potential Small-molecule Diagnostic Biomarkers Of Multiple Smentioning
confidence: 99%
“…In vivo 1 H MRS is a powerful non-invasive method for measuring the concentration of biochemicals in a pre-selected volume of interest. The biochemical profiles measured by 1 H MRS have been used to diagnose and characterise a variety of diseases (1)(2)(3)(4)(5)(6)(7). Non-invasive methods are of particular clinical importance in the study of childhood brain tumours, and 1 H MRS has been shown to provide information on tumour type, grade and prognosis (7)(8)(9) as well as being a promising tool for treatment monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Finalmente, otros autores han comprobado que la información cuantitativa aportada por las técni-cas de espectroscopía, como la disminución de los niveles del metabolito N-acetil aspartato (NAA) -que aparece predominantemente en placas crónicas y refleja destrucción neuronal-, puede ser también un buen predictor del rendimiento cognitivo en pacientes con EM [54,55]. Utilizando esta técnica, se muestran correlaciones significativas entre tests neuro psicológicos de aprendizaje verbal y planificación y disminuciones del NAA en zonas de la sustancia blanca periventricular [56], y un menor rendimiento en pruebas de memoria y disminución del NAA asociada al cingulado anterior [57]. Por otra parte, se ha asociado la peor ejecución en tests atencionales de escucha dicótica en pacientes con EM, con disminuciones en el NAA en la zona del sistema atencional activador del locus coeruleus [58].…”
Section: Nuevas Técnicas De Neuroimagen Estructural En El Estudio Delunclassified